Klinik Diş Hekimliğinin Bugünü - Kazan, Orhan; Doğan Çankaya, Tülin; Gönüldaş, Fehmi; Dündar, Burcu; Şentürk, Ayben; Balaban, Sena; Deniz Arısu, Hacer; Arslandaş Dinçtürk, Beyza; Kedici Alp, Cemile; Altuğ Yıldırım, Ayşenur; Topkaya, Nursima; Karakaş, Mert (Academician Publishing Book DOI Portal, 2023)
-